Aging in a Relativistic Biological Space-Time - Maestrini, Davide; Abler, Daniel; Adhikarla, Vikram; Armenian, Saro; Branciamore, Sergio; Carlesso, Nadia; Kuo, Ya-Huei; Marcucci, Guido; Sahoo, Prativa; Rockne, Russell C. (Frontiers in Cell and Developmental Biology, 2018)
Here we present a theoretical and mathematical perspective on the process of aging. We extend the concepts of physical space and time to an abstract, mathematically-defined space, which we associate with a concept of ``biological space-time'' in which biological clocks operate. We hypothesize that biological dynamics, represented as trajectories in biological space-time, may be used to model and study different rates of biological aging. As a consequence of this hypothesis, we show how the dilation or contraction of time resulting from accelerated or decelerated biological dynamics may be used to study precipitous or protracted aging. We show specific examples of how these principles may be used to model different rates of aging, with an emphasis on cancer in aging. We discuss the implications of this theory, including novel concepts that may improve our interpretation of biological aging.